Ferric carboxymaltose and SARS-CoV-2 vaccination-induced immunogenicity in kidney transplant recipients with iron deficiency: The COVAC-EFFECT randomized controlled trial - Vinke, Joanna Sophia J.; Altulea, Dania H. A.; Eisenga, Michele F.; Jagersma, Renate L.; Niekolaas, Tessa M.; van Baarle, Debbie; Heiden, Marieke van Der; Steenhuis, Maurice; Rispens, Theo; Abdulahad, Wayel H.; Sanders, Jan-Stephan F.; De Borst, Martin H. (Frontiers in Immunology, 2023)
Background: Kidney transplant recipients (KTRs) have an impaired immune response after vaccination against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Iron deficiency (ID) may adversely affect immunity and vaccine efficacy. We aimed to investigate whether ferric carboxymaltose (FCM) treatment improves humoral and cellular responses after SARS-CoV-2 vaccination in iron-deficient KTRs. Methods: We randomly assigned 48 iron-deficient KTRs to intravenous FCM (1-4 doses of 500mg with six-week intervals) or placebo. Co-primary endpoints were SARS-CoV-2-specific anti-Receptor Binding Domain (RBD) Immunoglobulin G (IgG) titers and T-lymphocyte reactivity against SARS-CoV-2 at four weeks after the second vaccination with mRNA-1273 or mRNA-BNT162b2. Results: At four weeks after the second vaccination, patients receiving FCM had higher plasma ferritin and transferrin saturation (P<0.001 vs. placebo) and iron (P=0.02). However, SARS-CoV-2-specific anti-RBD IgG titers (FCM: 66.51 [12.02-517.59] BAU/mL; placebo: 115.97 [68.86-974.67] BAU/mL, P=0.07) and SARS-CoV-2-specific T-lymphocyte activation (FCM: 93.3 [0.85-342.5] IFN-ɣ spots per 106 peripheral blood mononuclear cells (PBMCs), placebo: 138.3 [0.0-391.7] IFN-ɣ spots per 106 PBMCs, P=0.83) were not significantly different among both arms. After the third vaccination, SARS-CoV-2-specific anti-RBD IgG titers remained similar between treatment groups (P=0.99). Conclusions: Intravenous iron supplementation efficiently restored iron status but did not improve the humoral or cellular immune response against SARS-CoV-2 after three vaccinations.